معايير العمليات الإدارية في مدارس عدن الثانوية للموهوبين في الجمهورية اليمنية - صالح السعدي, محمد زين (University of Eloued جامعة الوادي, 2017)
هدف البحث إلى معرفة درجة توافر معايير العمليات الإدارية المتعلقة بـ(التخطيط – التنظيم والتنسيق – التوجيه والإرشاد – الرقابة والمتابعة – التقييم) في مدارس عدن الثانوية للموهوبين، واستخدم البحث المنهج الوصفي التحليلي، وتكونت عينة البحث جميع العاملين في مدارس عدن الثانوية للموهوبين (معلمين – إداريين)، البالغ عددهم (73) فرداً، وتوصل البحث إلى نتائج أهمها: - حصلت المحاور ككل على متوسط حسابي (2.28)، وانحراف معياري (0.50)، وكانت درجة توافر معايير العمليات الإدارية بمدارس عدن الثانوية النموذجية للموهوبين (قليلة). - لا توجد فروق ذات دلالة إحصائية عند مستوى الدلالة (α≤0.05) بين استجابات أفراد عينة البحث تجاه مدى توافر معايير العمليات الإدارية في مدارس عدن الثانوية للموهوبين تعزى للمتغيرات (نوع المدرسة – المسمى الوظيفي – سنوات الخبرة في مجال الموهوبين The aim of the research is to find out the availability of Standards for administrative processes in the Aden secondary school for gifted, and the research used descriptive analytical method, the sample consisted of all the workers in the typical Aden schools (teachers - administrative), the sample was (73)persons, and the research reached the following results: - The research axes obtained an average of (2.28), and a standard deviation (0.50), and the availability of standards for administrative processes in Aden secondary schools for gifted (few). -There are no statistically significant differences at the level of significance ).0.0≤α( between the responses of the research sample members to the availability of standards administrative processes due to variables (type of school - job title - years of experience in the field of gifted).
Availability of Standards for Administrative Processes in the Aden Secondary School for Gifted in the Republic of Yemen
مقال بمجلة الدراسات والبحوث الاجتماعية
Keywords: النمو المعرفي – صعوبات التعلم – طفل المدرسة الابتدائية; administrative processes, Aden secondary schools for gifted.